Hosta clausa (Asparagaceae) in East Asia: Intraspecific chloroplast genome variation and its phylogenomic implications - Jiyoung Yang; Seung-Chul Kim (PLoS ONE, 2025)
Hosta species are abundant in northeastern Asia, offering significant ornamental and horticultural value due to their diverse foliage colors and textures, as well as their showy, fragrant flowers. Among the eight taxa naturally distributed in Korea, H. clausa is found in central and northern Korea, as well as northeastern China, providing valuable resources for developing and improving new varieties. Currently, four intraspecific taxa of H. clausa are recognized at the variety level based on reproductive (opened vs. closed perianth), vegetative (leaf shape), and habitat characteristics: var. clausa, var. normalis, var. ensata, and var. geumgangensis. Despite its horticultural and taxonomic importance, little is known about the degree of intraspecific chloroplast genome variation and relationships among the varieties of H. clausa. This could provide some valuable information for marker-assisted breeding programs and molecular cultivar identification. In this study, we investigated the complete plastid genome of 14 accessions of H. clausa, covering its native distribution range. We characterized genome size and features and performed comparative plastome analyses (frequency of codon usage, nucleotide diversity, mutation hotspots). Our analysis revealed highly conserved structures and gene content organization in H. clausa, along with significantly (two to three times) lower nucleotide diversity compared to intraspecific herbaceous and woody species. The phylogenetic analysis did not support the recognition of intraspecific taxa as currently delimited, and a broad-scale geographical structure of complete plastomes was not apparent. The asexual reproductive mode of H. clausa appears to contribute to the low plastome genetic diversity. A total of 72 polymorphic sites identified among 14 accessions of H. clausa and their phylogenetic relationships, in conjunction with their geographical distribution and morphological characteristics, will be a valuable resource for barcoding study, marker-assisted breeding programs, and developing conservation strategies for hosta species in East Asia.